Physicochemical characterization of sediments from the coastal wetland of Samborombón Bay, Argentina - Carol, Eleonora S. (2012)
An exhaustive physicochemical characterization of sediments collected in the southern part of the coastal wetland of Samborombón Bay, Buenos Aires province, Argentina, was carried out to determine if the nitrogen and the phosphorus found derive from the organic matter. Samples were extracted from different geological environments: coastal plain, sand sheets, intertidal plain and water courses. Aspects analyzed involved the identification of mineralogical species present in sediments, distribution of grain size and specific surface. Major components were quartz and feldspars, while in some samples traces of calcite, hematite or kaolinite were found. As a novel fact, it is important to highlight that the ignition of sediments for organic matter valuation by weight loss was made between 200 and 500°C. In this way, the thermal breakdown and the exclusion of the released hydration water were assured. Likewise, it was established that specific surface is an aspect conditioned by the hydrology of the system. Standard techniques were used for the chemical analysis of organic carbon, nitrogen and phosphorus. The most abundant element was organic carbon (0.279–2.840%w/w), with nitrogen (0.200–0.522%w/w) and phosphorus (0.028–0.185%w/w) following in descending order. The results obtained show a different source for each of the two macronutrients studied: organic matter for nitrogen and inorganic substances for phosphorus. Finally, it was determined by means of the C:N ratio that the organic matter is of marine origin.